2020
DOI: 10.1016/j.bbih.2019.100024
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol induced NLRP3 inflammasome activation in the brain of rats is attenuated by ATRA supplementation

Abstract: Alcohol abuse affects several neurological pathways and causes significant alterations in the brain. Abstention from alcohol is an effective intervention against alcohol related diseases. But the recovery of the damaged cells to normal presents a major problem in those who have stopped alcohol consumption. Hence therapeutic interventions are needed. Our previous studies have shown that all trans retinoic acid (ATRA) is effective in reducing alcohol induced neuro toxicity. Chronic alcohol administration up-regu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…In contrast, in a murine model of alcohol-induced toxicity, an in vivo study showed that ATRA induced the downregulation of NLRP3, pro-caspase-1 and pro-IL-1β mRNAs in the brain tissue, upon endotoxin treatment. This report demonstrated that while chronic alcohol exposure increased the intestinal permeability for endotoxins, and subsequently elevated the ROS level in the circulation, ATRA developed a protective effect by inhibiting these mechanisms (98).…”
Section: Retinoic Acid Receptor (Rar)mentioning
confidence: 76%
“…In contrast, in a murine model of alcohol-induced toxicity, an in vivo study showed that ATRA induced the downregulation of NLRP3, pro-caspase-1 and pro-IL-1β mRNAs in the brain tissue, upon endotoxin treatment. This report demonstrated that while chronic alcohol exposure increased the intestinal permeability for endotoxins, and subsequently elevated the ROS level in the circulation, ATRA developed a protective effect by inhibiting these mechanisms (98).…”
Section: Retinoic Acid Receptor (Rar)mentioning
confidence: 76%
“…As the alcohol induced neuroinflammation in the brain, the IL-1β level increased through the activation of the NLRP3 inflammasome [ 66 ]. Our results demonstrated a pivotal role for NLRP3 inflammasome activation that mediates the IL-1β level in the alcohol-related neuroinflammation.…”
Section: Discussionmentioning
confidence: 99%
“…All these inflammatory mechanisms are enhanced by alcohol consumption. Ethanol has been reported to independently cause hyperactivation of STAT3, IKBα, and NLRP3 inflammasome both in vitro and in vivo [ 23 , 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%